Effect of different sources of nutrient on relative storability of coriander (Coriandrum sativum) seed - KUMAR, VINOD; TEHLAN, S K (The Indian Journal of Agricultural Sciences, 2020)
Accelerated aging is one of the most useful tests used for the estimation of relative storability of different seed lots. In the present study, coriander seed viability and vigour of coriander seed was estimated by putting different seed lots under various period of accelerated ageing, i.e. 24, 48, 72, 96 and 120 hours at 40±1°C at 100% relative humidity during two consecutive years, i.e. 2017 and 2018. The study was carried out on the seeds produced under eighteen treatment combinations of organic manures (Farmyard manure and vermicompost), bio-fertilizers (Azotobacter and phosphate solubilizing bacteria) and inorganic fertilizers. Experimental results revealed that the co-inoculation of Azotobacter and PSB along with application of 100% recommended dose of nitrogen through vermicompost (VC) recorded significantly higher standard germination (%), seedling length (cm), seedling dry weight (mg), vigour index-I and vigour index-II at every stage of accelerated ageing. The electrical conductivity recorded was also minimum under this treatment which was due to cell membrane stability and decreased leakage of solutes from the seeds.